2012
DOI: 10.1590/s1516-80342012000400013
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência do desvio fonológico em crianças da cidade de Salvador, Bahia

Abstract: OBJETIVO: Verificar a prevalência de desvio fonológico conforme idade, gênero e nível sócio econômico de crianças da cidade de Salvador, Bahia, Brasil. MÉTODOS: A amostra foi composta por 2880 crianças de ambos os gêneros, na faixa etária de 4 anos a 6 anos e 11 meses, de nível socioeconômico baixo, médio e alto, matriculadas nas escolas municipais de Salvador. Inicialmente, todas as crianças foram submetidas, de forma individual, à triagem fonoaudiológica e triagem auditiva. Além disso, foi realizada uma anam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 15 publications
5
11
1
6
Order By: Relevance
“…This finding does not corroborate studies that show that the higher the age the better is the phonological suitability [17][18][19] . This research corroborates a national study that showed that children aged five years presented higher prevalence of phonological deviations when compared to the four years old group 20 . In the present study the sample heterogeneity may have contributed to this result.…”
Section: Resultssupporting
confidence: 90%
“…This finding does not corroborate studies that show that the higher the age the better is the phonological suitability [17][18][19] . This research corroborates a national study that showed that children aged five years presented higher prevalence of phonological deviations when compared to the four years old group 20 . In the present study the sample heterogeneity may have contributed to this result.…”
Section: Resultssupporting
confidence: 90%
“…It is noteworthy that at the age of five, there was the largest number of complaints (15.8%). This result had been found previously and agrees on the literature 13 . Most patients live in the city of Porto Alegre, where the speech pathology clinic is located.…”
Section: Discussionsupporting
confidence: 94%
“…Most research previously reviewed agrees on the findings of the present study, whereby there is higher incidence of referrals to speech therapy for males [6][7][8][9][10][11][12][13] . The explanations for this finding are not consensual, and an author states that the brains of boys have slower maturation than those of girls 6 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Such fact disagrees with the literature 15,16 , which shows that phonological disorder happens more often among boys. There are studies where girls show better outcomes than boys with regard to tasks involving language skills [17][18][19][20][21] .…”
Section: Resultscontrasting
confidence: 99%